Targeting chemical and thermal stability of ovalbumin by simulated honey sugar cocktail - Wong, Y.H.; Kadir, H.A.; Tayyab, S. (Elsevier, 2015)
Effect of simulated honey sugar cocktail (SHSC) on chemical and thermal stability of ovalbumin (OVA) was investigated using multiple-spectroscopic techniques. Urea-induced denaturation of OVA produced a transition, characterized by the start-, the mid- and the end-points at 3.2M, 5.9/5.6M and 8.5/8.0M urea, respectively, when studied by MRE222nm and tryptophan fluorescence measurements. Presence of 10% or 20% (w/v) SHSC in the incubation mixture shifted the transition curve towards higher urea concentration in a concentration dependent manner. A comparison of far- and near-UV CD, UV-difference, ANS fluorescence and 3-D fluorescence spectral results of native OVA and 5.9M urea-denatured OVA (U-OVA), obtained in the absence and the presence of 20% (w/v) SHSC suggested SHSC-induced stabilization of U-OVA. Furthermore, a significant shift towards higher denaturant concentration was also noticed in the GdnHCl and thermal transition curves of OVA in the presence of 20% (w/v) SHSC. Taken together, all these results suggested stabilization of OVA against chemical and thermal denaturations by SHSC.